Comparison of actions of systemically and locally administrated local anaesthetics in diabetic rats with painful neuropathy. (11th October 2011) - Mert, Tufan; Gunes, Yasemin; Gunay, Ismail
Abstract Nothing is known about actions of levobupivacaine, a long‐acting local anaesthetic belonging to the amino amide group, in diabetes‐induced neuropathic pain conditions. In this study, we therefore investigated the possible antihyperalgesic and antiallodynic effects of levobupivacaine in diabetic animal model. Actions of systemically (intraperitoneal) or locally (intraplantar) administrated levobupivacaine on streptozotocin‐induced diabetic rats with painful neuropathy were examined using a thermal plantar test and a dynamic plantar aesthesiometer. Effects of levobupivacaine were compared with those of a well‐known amide local anaesthetic lidocaine. Levobupivacaine was more potent than lidocaine in all tests employed on diabetic rats. After intraperitoneal injections to diabetic rats, levobupivacaine, but not lidocaine, produced pronounced antihyperalgesic and antiallodynic effects. However, intraplantar administration of both levobupivacaine and lidocaine produced antihyperalgesic and antiallodynic action in diabetic rats. In contrast to the transient effects of lidocaine (30 min), antihyperalgesic and antiallodynic actions of levobupivacaine gradually disappeared within 120 min after intraplantar injections. Intraperitoneal or intraplantar administrations of levobupivacaine or lidocaine at the effective dose had no effect on any parameters in intact rats. Findings revealed that antiallodynic and antihyperalgesic potency of levobupivacaine was higher in comparison with that of lidocaine after their intraperitoneal or intraplantar administration to diabetic animals. Furthermore, locally administrated levobupivacaine has the greatest antihyperalgesic and antiallodynic actions in diabetic rats.